0
$\begingroup$

The i-th fitted value $\hat{Z}_i$ is written as a linear amalgam of response values $\hat{Z}_i=\sum_{j=1}h_{ij}Z_j$ where $h_{ij}=\frac{1}{n}+\frac{(y_i-\bar{y})(y_j-\bar{y})}{S_{yy}}$ and $S_{yy}=\sum_{i=1}(y_i-\bar{y})^2$.

I am trying to show $\sum_{j=1}h_{ij}^2=h_{ii}$ and $\sum_{j=1}h_{ij}y_j=y_i$; however, I am already stuck on the first one after doing the following.

$$ \begin{align} h_{ij}^2 &= \Bigg[\frac{1}{n}+\frac{(y_i-\bar{y})(y_j-\bar{y})}{S_{yy}}\Bigg]^2 \\ &= \frac{1}{n^2}+\frac{2}{n}\frac{(y_i-\bar{y})(y_j-\bar{y})}{S_{yy}}+\frac{(y_i-\bar{y})^2(y_j-\bar{y})^2}{S_{yy}^2} \\ &= \frac{S_{yy}^2}{n^2S_{yy}^2}+ \frac{2n}{n^2}\frac{S_{yy}(y_i-\bar{y})(y_j-\bar{y})}{S_{yy}^2} +\frac{n^2(y_i-\bar{y})^2(y_j-\bar{y})^2}{n^2S_{yy}^2} \\ &=\frac{S_{yy}^2+2nS_{yy}(y_i-\bar{y})(y_j-\bar{y})+n^2(y_i-\bar{y})^2(y_j-\bar{y})^2}{n^2S_{yy}^2} \\ &=\frac{\big[S_{yy}+n(y_i-\bar{y})(y_j-\bar{y})\big]^2}{n^2S_{yy}^2} \end{align} $$ I don't see how applying the summation $\sum_{j=1}$ to this leads to $h_{ii}=\frac{1}{n}+\frac{(y_i-\bar{y})^2}{S_{yy}}$. Am I missing something about what can be assumed or what is already known about $\sum_{j=1}(y_j-\bar{y})$ and $\sum_{j=1}(y_j-\bar{y})^2$?

$\endgroup$
2
$\begingroup$

Focus on your second line. First term: $$\sum_j\frac{1}{n^2}=\frac{n}{n^2}=\frac{1}{n}$$ Second term: $$\sum_j\frac{2}{n}\frac{(y_i-\bar{y})(y_j-\bar{y})}{S_{yy}^2}=\frac{2(y_i-\bar{y})}{nS_{yy}^2}\sum_j(y_j-\bar{y})=0$$ Third term: $$\sum_j\frac{(y_i-\bar{y})^2(y_j-\bar{y})^2}{S_{yy}^2}=\frac{(y_i-\bar{y})^2}{S_{yy}^2}\underbrace{\sum_j (y_j-\bar{y})^2}_{S_{yy}}=\frac{(y_i-\bar{y})^2}{S_{yy}}$$ When summed, the three terms give you $h_{ii}$.

$\endgroup$
  • $\begingroup$ Thanks, I have a bad habit of losing the forest from the trees so I apologize for the silly question. $\endgroup$ – strwars Oct 11 '19 at 11:04
  • $\begingroup$ @strwars you're welcome. It's not a silly one at all, you've asked your question the way it should be, i.e. by sharing your progress. $\endgroup$ – gunes Oct 12 '19 at 13:47
  • $\begingroup$ Thank you. If you don't mind I'm having a similar issue with proving $\sum_{j=1}h_{ij}y_j=y_i$. I have simplified the equation all the way to $\sum_{j=1}h_{ij}y_j=\bar{y}+\frac{(y_i-\bar{y})}{S_{yy}}\Bigg[\sum_{j=1}(y_j^2-\bar{y}^2)\Bigg]$, but cannot proceed further. It looks like I need $\sum_{j=1}(y_j^2-\bar{y}^2)=S_{yy}$, but I don't think I can make this happen. I tried introducing $2y_j\bar{x}-2y_j\bar{y}$ within the summation, but that gives me a $2\bar{y}^2n$ term I cannot seem to get rid of. $\endgroup$ – strwars Oct 13 '19 at 1:06
  • 1
    $\begingroup$ @strwars it’s best if you could post it as a separate question and share how you reached the final formula you have since it might be quite long for a comment (and maybe others can also help) $\endgroup$ – gunes Oct 13 '19 at 6:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.